Predicted Healthcare Demand and Health Inequalities among Brazilian Adult Population: A Propensity Score Weighted Approach (London Journal of Medical and Health Research, 2025)
The aim is to analyse how specific socio-demographic and health factors influence healthcare demand, considering the socio-economic differences in Brazil's adult population. The study focused on "expressed demand", i.e., individual's need for healthcare services and their ability to seek care. Overall, the Brazilian adult population had a 22.1% probability of requiring medical care within two weeks before the survey. An increasing gradient was observed from the poorest to the wealthiest deciles, with the wealthiest group having a 40% higher healthcare demand than the poorest. The main predisposing, enabling and need factors analysed were relevant in determining healthcare demand; however, they are strongly influenced by income disparities. In the Brazilian context of a universal and free access healthcare system, there is still a significant gap in healthcare demand through income distribution to the detriment of the poorest groups. Future research should focus on the impact of private health insurance on healthcare demand and spending. Monitoring the impact of private health insurance on healthcare utilisation is essential to ensure that provider profits do not influence healthcare demand.
Keywords: chronic pain.; biomarkers; opioid; opioid use disorder; neural alterations; Adults; Healthcare demand; Income inequalities; Propensity Score; Health Policy.